An experimental demonstration of a new type of proton computed tomography using a novel silicon tracking detector. Issue 11 (25th October 2016) - Taylor, J. T.; Poludniowski, G.; Price, T.; Waltham, C.; Allport, P. P.; Casse, G. L.; Esposito, M.; Evans, P. M.; Green, S.; Manger, S.; Manolopoulos, S.; Nieto‐Camero, J.; et al.
Abstract : Purpose: Radiography and tomography using proton beams promise benefit to image guidance and treatment planning for proton therapy. A novel proton tracking detector is described and experimental demonstrations at a therapy facility are reported. A new type of proton CT reconstructing relative "scattering power" rather than "stopping power" is also demonstrated. Notably, this new type of imaging does not require the measurement of the residual energies of the protons. Methods: A large area, silicon microstrip tracker with high spatial and temporal resolution has been developed by the Proton Radiotherapy Verification and Dosimetry Applications consortium and commissioned using beams of protons at iThemba LABS, Medical Radiation Department, South Africa. The tracker comprises twelve planes of silicon developed using technology from high energy physics with each plane having an active area of ∼10 × 10 cm segmented into 2048 microstrips. The tracker is organized into four separate units each containing three detectors at 60° to one another creating an x ‐ u ‐ v coordinate system. Pairs of tracking units are used to reconstruct vertices for protons entering and exiting a phantom containing tissue equivalent inserts. By measuring the position and direction of each proton before and after the phantom, the nonlinear path for each proton through an object can be reconstructed. Results: Experimental results are reported for tracking the path of protons with initial energies of 125 and 191 MeV. A spherical phantom of 75 mm diameter was imaged by positioning it between the entrance and exit detectors of the tracker. Positions and directions of individual protons were used to create angular distributions and 2D fluence maps of the beam. These results were acquired for 36 equally spaced projections spanning 180°, allowing, for the first time, an experimental CT image based upon the relative scattering power of protons to be reconstructed. Conclusions: Successful tracking of protons through a thick target (phantom) has demonstrated that the tracker discussed in this paper can provide the precise directional information needed to perform proton radiography and tomography. When synchronized with a range telescope, this could enable the reconstruction of proton CT images of stopping power. Furthermore, by measuring the deflection of many protons through a phantom, it was demonstrated that it is possible to reconstruct a new kind of CT image (scattering power) based upon this tracking information alone.